MODERN SPORT: PROBLEMS AND SOLUTIONS - Karimov Bekzod Boyqobilovich (Proximus Journal Publishing, 2024)
Modern sport represents a multifaceted industry, encompassing both mass and elite sports, playing an important role in society. At the same time, its development faces several issues, including the myth that sport is the main factor for maintaining and improving health, the dangers of intense physical exertion, early specialization of children, corruption, and the use of doping. This article explores the key contradictions in modern sport and proposes solutions through the improvement of sports equipment, training methods, athlete selection systems, and health prevention strategies. It is expected that addressing these problems will improve sports education and create a positive public image of sports.
Keywords: modern sport; elite sport; Olympic and professional sport,